DISTRIBUSI ZAKAT UNTUK GOLONGAN FAQIR UZUR PADA LEMBAGA BAITUL MAL DI ACEH - Ida Friatna (Universitas Islam Negeri Ar-Raniry, 2019)
This is an obligation to a certain Muslim who meet the requirement to pay zaka. In the other side, the government needs to operate an authorized institution to manage this kind of alms, including infaq and other Muslim’s alms. Int this case, the government of Aceh has established a kind of Islamic treasury office named Baitul Mal which mandated to preserve, manage, and develop the zaka, infaq, waqf, and other alms in Islam, including the preservation of Islamic custody. This study examines the zaka distribution by Baitul Mal office to the old poor beneficiary group. Islam basically distinguishes between miskin and faqir based on their different level, where the faqr is they are in a poorer condition. Currently, the Baitul Mal office separates the poor group into two types, namely the old poor (Faqir uzur) and the normal poor (Non-old faqir). The old poor is defined as people with old age, long sickness, and permanent disable, or with other condition they become not productive. The catagorization has consequences to the distribution portion. The Baitul Mal decided monthly consumptive distribution to the old poor group and to the normal poor is also giving incidentally by the consumptive method. This arrangement is aimed to be a guidance for all the Baitul Mal around the regencies level in targeting those types of faqr. So, here are main questions why do the Baitul Mal make this distinction and what is the impact to both type of faqr life. This study found that the Baitul mal wanted to be committed to elevating the faqr life through zaka distribution, especially to the faqr uzur that considered unproductive people and the distribution was chosen by consumptive way. This study learned that the Baitul Mal also considered to distributing part of zaka productively. The study uses the literatures and also the Baitul Mal official data.